Urgensi Penguatan Pengawasan Terhadap Kolaborasi antara Bank Dengan Fintech Lending Dalam Sistem Hukum Perbankan di Indonesia - Aini, Ailia Nur; Putri, Amelia Juliana; Adhnin, Ghariza Ardhia; Girsang, Rachel; B, Baidhowi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Collaboration between banking and fintech lending or online loans is a development that continues to emerge in the Indonesian financial system. On the one hand, this collaboration offers inclusive and efficient financial service innovations, but on the other hand it raises potential legal, operational, and consumer protection risks that have not been fully anticipated by the existing supervisory framework. This article examines the urgency of strengthening legal supervision of this collaboration, with an emphasis on regulatory gaps, overlapping supervisory authorities, and challenges in ensuring compliance with the principles of prudence and transparency. This study uses a normative legal approach with an analysis of laws and regulations, financial institution decisions, and case studies of bank-fintech collaboration. The results of the study indicate that strengthening supervision is needed through regulatory harmonization between the OJK and Bank Indonesia, affirmation of integrated supervisory mechanisms, and updates to digital risk-based policies. With this strengthening, the Indonesian banking legal system is expected to be able to accommodate the development of financial technology adaptively while protecting the stability of the financial system and consumer interests.